Institutional Ownership, Firm Size, and Agency Cost: A Moderating Role of Leverage - Evalina, Evlin; Gusni, Gusni (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
Agency fees are a form of internal company costs borne by shareholders to oversee and control the activities of agents. These costs arise from core dissatisfaction, inefficiency, and disruption. The agent is given the authority to act on behalf of the principal. These agency costs exist to overcome agency conflicts. This study aims to analyze the assessment of institutional ownership and company size on agency costs with leverage as a variable moderation in state-owned enterprises that appear on the Indonesian securities market. This study constitutes applied research that employs a quantitative methodology and employs secondary data. The count of samples determined by purposive sampling method was 13 companies, from 2018-2022. The method applied in the research involves panel data regression with a random effect specification. The model chosen from the research results is the Fixed Effect. The research results revealed that institutional ownership has a positive impact on agency costs. Firm size has a negative impact on agency costs and leverage only moderates institutional ownership by weakening the impact of institutional ownership on agency costs. Keywords: Agency Conflict; Institutional Ownership; Firm Size; Leverage; Agency Cost